2016
DOI: 10.7150/ijms.15951
|View full text |Cite
|
Sign up to set email alerts
|

Adding Biotin to Parenteral Nutrition Solutions Without Lipid Accelerates the Growth of Candida albicans

Abstract: Background: We have previously demonstrated that Candida albicans requires multivitamins (MVs) or lipid to increase rapidly in parenteral nutrition (PN) solutions. In this study, in detail, the effects of vitamins on the growth of C. albicans in PN solutions without lipid were investigated. Methods: In the 1st experiment, a commercial PN solution without lipid was supplemented with water-soluble vitamins (SVs: vitamins B1, B2, B6, B12 and C, folic acid, nicotinamide, biotin and panthenol), water-insoluble vita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Patients with PVC-BSIs caused by S. aureus tend to have a higher rate of complicated bacteremia and greater overall mortality than patients with infections caused by other pathogens (8). C. albicans can also rapidly proliferate in PPN solutions (12,19), and water-soluble vitamins without lipids, particularly biotin, promote the growth of C. albicans (19). Our study showed that PVC-BSIs caused by S. aureus and Candida species were more commonly identified in patients receiving PPNs than those with a peripheral catheter but no PPN.…”
Section: Roc Curve For the Combination Of An Average Daily Infusion T...mentioning
confidence: 99%
“…Patients with PVC-BSIs caused by S. aureus tend to have a higher rate of complicated bacteremia and greater overall mortality than patients with infections caused by other pathogens (8). C. albicans can also rapidly proliferate in PPN solutions (12,19), and water-soluble vitamins without lipids, particularly biotin, promote the growth of C. albicans (19). Our study showed that PVC-BSIs caused by S. aureus and Candida species were more commonly identified in patients receiving PPNs than those with a peripheral catheter but no PPN.…”
Section: Roc Curve For the Combination Of An Average Daily Infusion T...mentioning
confidence: 99%